Lena Horne - Palmer, Leslie; Huggins, Nathan Irvin, 1927- (New York : Chelsea House Publishers, 1989)
Describes the life and career achievements of the African-American singer.
Includes discography (p. 122), bibliographical references (p. 124), and index.
Wilson's Junior High School.
8.0
5-8
7-9
Keywords: Horne, Lena -- Juvenile literature; Horne, Lena; Horne, Lena; African American singers -- Biography -- Juvenile literature; Singers -- United States -- Biography -- Juvenile literature; African Americans -- Biography; Singers; African Americans -- Biography; Singers -- Biography